Improving the patient experience through patient portals: Insights from experienced portal users - Cynthia Sieck; Jennifer Hefner; Ann McAlearney (The Beryl Institute, 2018)
Background: Patient portals have become part of the ecosystem of care as both patients and providers use them for a range of activities both individually and collaboratively. As patients and providers gain greater experience using portals, their use and needs related to portals may evolve. Objective: This study aimed to learn from experienced patient portal users to improve our understanding of their perspectives on portal use for collaboration and engagement as well as explore how using a portal influenced their experiences with primary care providers. Methods: Qualitative study involving 29 semi-structured interviews with family medicine patients from a large Academic Medical Center (AMC). Interviewees were patients with chronic conditions who had been identified by their providers as experienced portal users. Interview transcripts were analyzed using rigorous qualitative methods. Results: Common themes emerged around both logistical and psychological benefits of portal use. Logistical benefits included increased efficiency, improved ability to track their health information, and better documentation of communications and information during and between office visits. Psychological benefits were a greater sense of collaboration in care, increased trust in providers, and enhanced engagement in health care activities. Conclusion: Experienced portal users discussed ways in which patient portals improved both their ability to manage their care and their relationships with providers. Frequent users described a sense of collaboration with their providers and greater trust in the relationship. These findings suggest that portal use may be a mechanism through which patients can increase patient engagement and improve the patient experience.